Hubungan antara Olahraga Hamil dengan Nyeri Punggung pada Ibu Hamil Trimester III: The Relationship between Pregnancy Exercise and Back Pain in Third Trimester Pregnant Women - Ilawati, Sri; Susanti, Novi; Hasibuan, Namiroh Falah; Pakpahan, Asima Lamtiar (Jurnal Abdi Keperawatan dan Kedokteran, 2025)
Back pain is a common complaint among pregnant women, particularly in the third trimester, which can affect their quality of life and readiness for childbirth. One non-pharmacological method believed to alleviate this complaint is prenatal exercise. The aim of this study was to determine the relationship between the practice of prenatal exercise and the occurrence of back pain in third-trimester pregnant women. This study employed a descriptive-analytic design with a cross-sectional approach. The population consisted of all third-trimester pregnant women who visited healthcare facilities in Medan. Sampling was conducted using accidental sampling, resulting in 36 respondents. The independent variable was the practice of prenatal exercise, while the dependent variable was the occurrence of back pain. Data were collected using a closed-ended questionnaire and a subjective pain observation sheet. Data analysis was conducted using the Chi-square test with a significance level of 0.05. The results showed that out of 36 respondents, 61.1% did not participate in prenatal exercise, and 69.4% experienced back pain. Statistical analysis indicated a significant relationship between prenatal exercise and the occurrence of back pain in third-trimester pregnant women, with a p-value of 0.000 (<0.05). In conclusion, there is a significant association between prenatal exercise and back pain in third-trimester pregnant women. Therefore, it is recommended that prenatal exercise be integrated into antenatal care programs as a promotive and preventive intervention. Regular education from healthcare professionals is essential to increase pregnant women's awareness and encourage consistent participation in prenatal exercise to reduce the risk of back pain.